Association between Intrauterine Growth Restriction and Pregnancy Hypertension - Nada Ardilla Dwiayu Febrina; Aris Primadi; Bony Wiem Lestari (Althea Medical Journal, 2016)
Background: Intrauterine Growth Restriction (IUGR) certainly poses health problems that leads to increase mortality and can cause mental and physiological disturbances to the infants. Reduced organ perfusion is one of the etiologies of IUGR which is caused by placenta obstruction. This happens because of pregnancy hypertension as a risk factor. Furthermore, educational level, employment status, parity, and anemia are also its risk factors. The objective of this study was to analyze the prevalence of IUGR and association between IUGR and pregnancy hypertension.